Diarylprolinol in an Asymmetric, Direct Cross‐Aldol Reaction with Alkynyl Aldehydes. Issue 10 (26th July 2013) - Hayashi, Yujiro; Kojima, Masahiro; Yasui, Yusuke; Kanda, Yuta; Mukaiyama, Takasuke; Shomura, Hiroki; Nakamura, Daichi; Ritmaleni,; Sato, Itaru
Abstract The direct cross‐aldol reaction of alkynyl aldehydes catalyzed by a trifluoromethylated diarylprolinol provides a practical route for the highly enantioselective synthesis of chiral β‐alkynyl‐β‐hydroxy aldehydes. Good anti selectivity and excellent enantioselectivity were obtained in the reactions of silylpropynals, which afford synthetically useful chiral building blocks.